Challenges, opportunities and legacies: experiencing the internationalising of UK planning curricula across space and time. Issue 5 (1st September 2020) - Adams, David; Andres, Lauren; Denoon-Stevens, Stuart Paul; Melgaço, Lorena
Abstract : Drawing on interviews with selected UK planning academics and survey results from current planning practitioners, this article provides valuable and timely perspectives on how internationalisation is experienced by those within and beyond the immediate institutional context. Although internationally focused planning education helps planners tackle the manifold urban challenges in the global South, the article goes on to argue that relational approaches hold much promise for planners working in so-called developed countries, including the UK, to understand the diverse needs of different diasporic communities. Such knowledge is crucial to develop sustainable planning solutions in the face of uneven processes of urban development.